2018
DOI: 10.1007/s12350-017-0887-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in dual respiratory and ECG-gated SPECT imaging

Abstract: In the current issue of Journal of Nuclear Cardiology, Kortelainen et al report that a new method of acquiring dual respiratory and ECG-gated SPECT myocardial perfusion data reduces artifacts due to respiratory motion while leaving asynchrony measurements derived from the data unaltered. 1 As the improvements reported were modest and only observed in a subset of subjects, a relevant question to ask is whether the additional equipment needed and patient preparation logistics would significantly improve patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…23 Electrocardiogram gating to exclude arrhythmic heartbeats is essential when imaging a beating heart and further correction of respiratory motion might improve image quality and patient-by-patient variability. 24 26 However, the combined effects of such corrections have yet to be determined and they are not necessarily applied in clinical practice. We found that the integrated corrections for the SPECT images using a list-mode data acquisition are technologically and clinically feasible and significantly improved image quality by visual assessment without any noticeable pitfalls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Electrocardiogram gating to exclude arrhythmic heartbeats is essential when imaging a beating heart and further correction of respiratory motion might improve image quality and patient-by-patient variability. 24 26 However, the combined effects of such corrections have yet to be determined and they are not necessarily applied in clinical practice. We found that the integrated corrections for the SPECT images using a list-mode data acquisition are technologically and clinically feasible and significantly improved image quality by visual assessment without any noticeable pitfalls.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, although improving quantitative values by integrating all possible correction methods is desirable, whether pursuing true quantitation would definitively improve clinical diagnostic ability requires further investigation. 26 …”
Section: Discussionmentioning
confidence: 99%